Demokratisasi dalam Rangka Pembangunan Hukum Responsif - Sanusi, Sanusi; Idayanti, Soesi; Widyastuti, Tiyas Vika (Universitas Pancasakti Tegal, 2020)
This research is conceptual research that intends to examine the idea of democracy in progressive legal development. As a means of state policy, the development of laws carries a variety of implications. During that time the law was only understood as a rigid rule and put too much emphasis on aspects of the legal system regardless of the relationship between the law and the issues that had to be addressed, such as social issues. The law is synonymous with the order as a mirror of the regulation of the ruler, on the other hand, there is also an understanding of the law that emphasizes more on the legitimacy aspect of the rule itself. Responsive law is results-oriented, i.e. on goals that will be achieved outside the law. A hallmark of responsive law is the search for implied values contained in rules and policies. In this responsive legal model, they express disapproval of what they consider to be standardized and inflexible interpretations. Legal products that are responsive to the manufacturing process is democratic, namely participation, which invites the participation of as many elements of society as possible, both in terms of individuals, and community groups, and must also aspire to come from the wishes or desires of the community. This means that the product of the law is not the authority of the ruler to simply legitimize his power.